Building a prosperous Southeast Asia : - Yoshihara, Kunio (Curzon Press, 1999)
This book introduce about economic crisis: how serious is it and how did it all begin? Don't think retro!, Government shoud specialize and strengthen, Reinventing culture, Brave the future